Implementation of a Web-Based Asset Information System to Enhance Efficiency and Transparency in Asset Management at Gampong Tingkeum, Aceh Besar Regency: Implementasi Sistem Informasi Aset Berbasis Web untuk Peningkatan Efisiensi dan Transparansi Pengelolaan Aset di Gampong Tingkeum, Kabupaten Aceh Besar - Safrizal Razali; Al Bahri; Safrizal Z.A; Maimun; Yuwaldi Away; Kahlil Muchtar (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Asset management is a crucial aspect of governance at the village level. Gampong Tingkeum, Aceh Besar Regency, faces issues with asset recording, which is still done manually without proper codification and labeling. This study aims to design and implement a web-based asset information system to improve the efficiency, accuracy, and transparency of asset management in the village. The system was developed using the Waterfall method with a Prototype approach, utilizing the CodeIgniter framework and MySQL database. The implementation process included system installation, configuration, and training for village officials on system usage. The system was tested using Black Box Testing and User Acceptance Testing (UAT), which showed that it successfully performed asset recording, codification, labeling, and reporting functions. The implementation results demonstrated improvements in time efficiency, data accuracy, as well as increased transparency and accountability in asset management. This system is expected to serve as a model for modern and structured village asset management, aligned with the latest regulations of Permendagri No. 3 of 2024.